Integrating energy and land-use planning: Socio-metabolic profiles along the rural-urban continuum in Catalonia (Spain) (2014)
Abandoning fossil fuels and increasingly relying on low-density, land-intensive renewable energy will increase demand for land, affecting current global and regional rural–urban relationships. Over the past two decades, rural–urban relationships all over the world have witnessed unprecedented changes that have rendered their boundaries blurred and have lead to the emergence of “new ruralities.” In this paper, we analyze the current profiles of electricity generation and consumption in relation to sociodemographic variables related to the use of time and land across the territory of Catalonia, Spain. Through a clustering procedure based on multivariate statistical analysis, we found that electricity consumption is related to functional specialization in the roles undertaken by different types of municipalities in the urban system. Municipality types have distinctive metabolic profiles in different sectors depending on their industrial, services or residential role. Villages’ metabolism is influenced by urban sprawl and industrial specialization, reflecting current “new ruralities.” Segregation between work activity and residence increases both overall electricity consumption and its rate (per hour) and density (per hectare) of dissipation. A sustainable spatial organization of societal activities without the use of fossil fuels or nuclear energy would require huge structural and sociodemographic changes to reduce energy demand and adapt it to regionally available renewable energy.